Pengaruh Etika Kerja Islami, Motivasi Kerja Islami dan Lingkungan Kerja Islami Terhadap Kinerja Karyawan (Studi Kasus Karyawan Bank Muamalat KC Serang) - Triana Julianti; Moh Mukhsin; Ahyakudin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to determine the effect of Islamic Work Ethics, Islamic Work Motivation, and an Islamic Work Environment on Employee Performance at Bank Muamalat Serang Branch. The study used a quantitative approach, distributing questionnaires to employees as respondents, and multiple linear regression analysis was used to test the relationship between variables using SPSS 25. The results showed that the three variables: Islamic Work Ethics, Islamic Work Motivation, and an Islamic Work Environment, had a positive and significant effect, both partially and simultaneously, on employee performance. This finding confirms that the application of Islamic values ​​in the work culture can improve employee performance at Islamic financial institutions. Keywords: Islamic Work Ethics, Islamic Work Motivation, Islamic Work Environment, Employee Performance